The Role of Streamers on Consumers’ Impulsive Buying in Shopee Live: Implementation of the S-O-R Model - Salsabila Salma; Maulana Agung; May Roni (International Journal of Economics, Business and Innovation Research, 2024)
The rapid growth of live stream technology in e-commerce has emerged as an interesting phenomena in marketing. Live streaming in e-commerce has transformed online shopping behavior to be more dynamic and interactive. Live commerce enables consumers to engage in a more personalized shopping experience via real-time interactions with streamers. This study attempts to determine the extent of the impact that streamers' social presence has on consumer impulse buying behavior. This study implemented the S-O-R model to analyze consumer behavior construction, using the streamer's social presence as the stimulus, the flow state and customer trust as the organism, and predicting impulsive buying behavior as the expected response. Survey methods and SEM-PLS analytical techniques are employed to examine the correlation among latent variables. This study examined 100 Shopee Live consumers and discovered that the social presence of streamers strongly impacted flow state and consumer trust, which subsequently had significant impact on consumer impulse buying behavior on Shopee Live.